Staging Social Justice : Collaborating to Create Activist Theatre - Nadon, Daniel-Raymond, 1960-; Bowles, Norma, 1961- (Book collections on Project MUSE., 2013)
Fringe Benefits, an award-winning theatre company, collaborates with schools and communities to create plays that promote constructive dialogue about diversity and discrimination issues. This book is a collection of essays about Fringe Benefits' script-devising methodology and their collaborations in the United States, Australia, Canada and the United Kingdom. The anthology also vividly describes the transformative impact of these creative initiatives on participants and audiences. By reflecting on their experiences working on these projects, the contributing writers - artists, activists and scholars - provide the reader with tools and inspiration to create their own theatre for social change.